A Case Report: The Diagnosis and Therapeutic Evaluation for a Rare Disease of Langerhans Cell Histiocytosis Involving Thyroid. Issue 44 (November 2015) - Cai, Ye-Feng; Wang, Qing-Xuan; Ni, Chun-Jue; Dong, Si-Yang; Lv, Lin; Li, Quan; Chen, En-Dong; Zhang, Xiao-Hua
Abstract : Abstract: Langerhans cell histiocytosis (LCH) involving the thyroid gland is extremely rare. Currently, the diagnosis and therapeutic evaluation for LCH involving thyroid is a challenge. We reported a rare case of LCH involving thyroid, presenting as painless thyroid goiters, and successfully performed positron emission tomography/computed tomography (PET/CT) to make an accurate diagnosis and therapeutic evaluation for LCH. Although the histology or cytology is the golden standard for the diagnosis of LCH involving thyroid, the PET/CT should be keep in mind when LCH involving thyroid with inconclusive cytologic results. During the treatment of LCH, PET/CT can be performed to assess the therapeutic effect and select the most effective and reliable treatment for LCH.